Menjawab Tantangan Pendidikan Anak Usia Dini dengan Pendidikan Perspektif Islam - M. Fauzi (Alzam: Journal of Islamic Early Childhood Education, 2024)
A complete human being" is the main goal of Islamic education. To achieve this goal, it should be prepared carefully starting as early as possible. Considering that the golden age is an important period and determines the success of children's education towards the expected results. However, there are many challenges that must be faced by parents and educators during this period of education, including first, the symptoms of hedonism that plague modern education; second, the escalation of violence against children; third, the lack of exemplary and unbalanced communication between parents and children. In the Islamic perspective, there are five models of education that are worth choosing for children's growth and development. First, education through example (at-tarbiyah bil-qudwah); second, education through habits (at-tarbiyah bil-adah); third, education through advice (al-tarbiyah bil-mauidhah); fourth, education through supervision (al-tarbiyah bil-mulahadhah) and fifth, education through sanctions (al-tarbiyah bil-uqubah).